An attempt at standardization of nursing care of patients after operation for colorectal cancer - Laska, Edyta (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2008)
Preparation of standards of nursing care is an important step in the developing of nursing. This matter is a starting point for further development of medical studies and should be constantly improved both with the increased knowledge and practices present in that field. The standards are intended to uncover deficiencies and anomalies in medical care. The standard establishes the level of nursing care relevant for the applicable group of patients. Additionally it raises objectivity in the assessment of the current level of care and encourages further development of professional skills. At present colorectal cancer is the most common cancer of the alimentary canal and the second most common cancer of all (in both women and men).